2014
DOI: 10.1037/a0037189
|View full text |Cite
|
Sign up to set email alerts
|

Premorbid adjustment profiles in psychosis and the role of familial factors.

Abstract: Disease heterogeneity in patients with psychotic disorder may be explained by distinct profiles of premorbid adjustment. The current study explored premorbid adjustment profiles in patients with psychotic disorders, associations with cognitive and clinical characteristics after disease onset, and the role of familial factors. A total of 666 patients with psychosis (predominantly schizophrenia), 673 siblings, 575 parents, and 585 controls were included in this study. Cluster analyses were performed on the patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 33 publications
3
16
1
Order By: Relevance
“…Unaffected relatives also differed from healthy controls, although to a lesser extent than patients, by showing a poorer early adjustment only for the academic domain and independently of the age period, as well as a slightly greater frequency of poor early adjustment. These findings, in line with those of other studies exploring early adjustment in patients' relatives (4)(5)(6)(7)(8)64), support the hypothesis that poor early adjustment may represent a marker of vulnerability to schizophrenia.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Unaffected relatives also differed from healthy controls, although to a lesser extent than patients, by showing a poorer early adjustment only for the academic domain and independently of the age period, as well as a slightly greater frequency of poor early adjustment. These findings, in line with those of other studies exploring early adjustment in patients' relatives (4)(5)(6)(7)(8)64), support the hypothesis that poor early adjustment may represent a marker of vulnerability to schizophrenia.…”
Section: Discussionsupporting
confidence: 90%
“…In line with the neurodevelopmental hypothesis of schizophrenia, a poor premorbid adjustment has been widely reported in individuals affected by the disorder (1)(2)(3). Moreover, an impairment of functioning in early epochs of life has been described in unaffected relatives of patients with schizophrenia as compared to healthy controls (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 81%
“…Those with a declining social course had fewer friends and greater negative symptoms after disease onset, and those with worse childhood academic adjustment achieved less education and had poorer working memory. Quee et al (2014) identified six clusters based on social and academic PMA, ranging from "normal" to "overall impaired." Horton et al (2015) found three clusters of PMA trajectories in a sample of first-episode patients.…”
Section: Introductionmentioning
confidence: 99%
“…Another important question is whether childhood trauma acts on its own or whether other risk factors moderate or mediate its effect on premorbid adjustment. Other risk factors include, amongst others, obstetric complications [18], neurological soft signs, substance abuse [18] and a family history of the illness [19]. …”
Section: Introductionmentioning
confidence: 99%